2006
DOI: 10.1186/1477-7517-3-33
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Background: Very little is known about female injecting drug users (IDU) in Bangladesh but anecdotal evidence suggests that they are hidden and very vulnerable to HIV through both their injection sharing and sexual risk behaviors. In order to better understand the risks and vulnerability to HIV of female IDU, a cohort study was initiated through which HIV prevalence and risk behaviors was determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 28 publications
2
19
0
Order By: Relevance
“…Overlap between sex work and injecting drug use is especially high in parts of Eastern Europe and Central Asia and is a growing concern in some Latin American countries, such as Mexico (El-Bassel et al, 2014a; Morris et al, 2013). Women engaging in both the sex trade and use of illicit drugs are more likely to share needles/syringes and other injection paraphernalia amongst themselves and their clients, have unprotected sex with their clients as well as their intimate partners, have higher rates of STIs and they are also more likely to experience sexual violence and incarceration (Azim et al, 2006; Des Jarlais, Feelemyer, Modi, Arasteh, & Hagan, 2012; N. El-Bassel, S. A. Shaw, A. Dasgupta, & S. A. Strathdee, 2014b).…”
Section: Women Drug Use and Sex Workmentioning
confidence: 99%
“…Overlap between sex work and injecting drug use is especially high in parts of Eastern Europe and Central Asia and is a growing concern in some Latin American countries, such as Mexico (El-Bassel et al, 2014a; Morris et al, 2013). Women engaging in both the sex trade and use of illicit drugs are more likely to share needles/syringes and other injection paraphernalia amongst themselves and their clients, have unprotected sex with their clients as well as their intimate partners, have higher rates of STIs and they are also more likely to experience sexual violence and incarceration (Azim et al, 2006; Des Jarlais, Feelemyer, Modi, Arasteh, & Hagan, 2012; N. El-Bassel, S. A. Shaw, A. Dasgupta, & S. A. Strathdee, 2014b).…”
Section: Women Drug Use and Sex Workmentioning
confidence: 99%
“…Studies in all regions of the world have reported on the high prevalence of violence suffered by people selling sex (10,22,23,24). It appears to be closely related to context, with isolated workers or workers in public places being most at risk.…”
Section: Violencementioning
confidence: 99%
“…Our reviewed articles also show the consistent violent culture among DU-FSWs. Drug use among both FSWs and their clients exacerbated gender-based violence, as drug use jeopardized the women's negotiating power in selecting clients and implementing safe sex practices (Parry et al, 2009;Strathdee, et al, 2011), placed them at a greater risk of HIV/STIs (Azim et al, 2006), and often made clients more violent due to their frustrations with impotence (Leggett 2001). Furthermore, compared to their peers who did not use drugs, DU-FSWs were more likely to experience psychological distress, which put the women at enhanced risk for HIV infection (Tang et al, 2014;Seth et al, 2009;Ulibarri, Strathdee, Patterson, 2010).…”
Section: Sex-related Hiv Riskmentioning
confidence: 99%
“…Most quantitative studies used cross-sectional design (34/37) and only three were cohort studies (Azim et al, 2006;Weber et al, 2002;Vioque et al, 1998). The majority of the studies recruited research participants through STI clinics or other related local community settings (e.g., AIDS outreach offices, HIV-outpatient facilities, national sentinel surveillance sites).…”
Section: Study Design and Samplingmentioning
confidence: 99%